2023
DOI: 10.3347/phd.23088
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis-associated genes in Acanthamoeba castellanii feeding on Escherichia coli

Min-Jeong Kim,
Eun-Kyung Moon,
Hye-Jeong Jo
et al.

Abstract: Acanthamoeba species are free-living amoebae those are widely distributed in the environment. They feed on various microorganisms, including bacteria, fungi, and algae. Although majority of the microbes phagocytosed by Acanthamoeba spp. are digested, some pathogenic bacteria thrive within them. Here, we identified the roles of 3 phagocytosis-associated genes (ACA1_077100, ACA1_175060, and AFD36229.1) in A. castellanii. These 3 genes were upregulated after the ingestion of Escherichia coli. However, after the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2A ), is induced in A. castellanii trophozoites fed with E. coli DH5α ( 40 ). Interestingly, Kim et al ( 41 ) reported that silencing of ACA1-077100, which encodes XP_004335869.1 annotated as Rab1/RabD family small GTPase, disabled phagosome formation in A. castellanii fed with Escherichia coli . Currently, there are no reports on the downstream effectors recruited by Acanthamoeba Rabs for phagosome maturation and delivery to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A ), is induced in A. castellanii trophozoites fed with E. coli DH5α ( 40 ). Interestingly, Kim et al ( 41 ) reported that silencing of ACA1-077100, which encodes XP_004335869.1 annotated as Rab1/RabD family small GTPase, disabled phagosome formation in A. castellanii fed with Escherichia coli . Currently, there are no reports on the downstream effectors recruited by Acanthamoeba Rabs for phagosome maturation and delivery to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Rab repertoire of A. castellanii strain Neff was studied in the context of phylogenomic and evolutionary analyses, and it was estimated that it encodes 93 Rabs ( 38 , 39 )⁠. However, as detailed in the discussion, only two publications exist on the functional characterization of Acanthamoeba Rab GTPases ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%